Contrasting nutrient–disease relationships: Potassium gradients in barley leaves have opposite effects on two fungal pathogens with different sensitivities to jasmonic acid. (29th June 2018) - Davis, Jayne L.; Armengaud, Patrick; Larson, Tony R.; Graham, Ian A.; White, Philip J.; Newton, Adrian C.; Amtmann, Anna
Abstract: Understanding the interactions between mineral nutrition and disease is essential for crop management. Our previous studies with Arabidopsis thaliana demonstrated that potassium (K) deprivation induced the biosynthesis of jasmonic acid (JA) and increased the plant's resistance to herbivorous insects. Here, we addressed the question of how tissue K affects the development of fungal pathogens and whether sensitivity of the pathogens to JA could play a role for the K–disease relationship in barley ( Hordeum vulgare cv. Optic). We report that K‐deprived barley plants showed increased leaf concentrations of JA and other oxylipins. Furthermore, a natural tip‐to‐base K‐concentration gradient within leaves of K‐sufficient plants was quantitatively mirrored by the transcript levels of JA‐responsive genes. The local leaf tissue K concentrations affected the development of two economically important fungi in opposite ways, showing a positive correlation with powdery mildew ( Blumeria graminis ) and a negative correlation with leaf scald ( Rhynchosporium commune ) disease symptoms. B. graminis induced a JA response in the plant and was sensitive to methyl‐JA treatment whereas R. commune initiated no JA response and was JA insensitive. Our study challenges the view that high K generally improves plant health and suggests that JA sensitivity of pathogens could be an important factor in determining the exact K–disease relationship. Abstract : Jasmonic acid (JA) is a plant hormone with important roles in leaf senescence and pathogen defence. Our finding that JA biosynthesis is up‐regulated by low concentrations of potassium (K) in leaves suggests that JA may provide the molecular link between plant K status and fungal disease. This hypothesis was further supported by the finding that disease symptoms on barley leaves were positively correlated with leaf K content for the JA‐sensitive powdery mildew ( Blumeria graminis ) but negatively correlated with leaf K content for the JA‐insensitive leaf scald ( Rhynchosporium commune ).